A study of Minangkabau architecture in two regions : West Sumatra, Indonesia, and Negeri Sembilan, Malaysia - Abdullah, Fadzidah; Wongso, Jonny (Centre of the Study of Architecture in the Arab Region (CSAAR), 2007)
This research deals with a study of regional architecture in two (2) regions of two (2) countries: West Sumatra, Indonesia, and Negeri Sembilan, Malaysia. Both regions are said to have very similar regional architecture as some of the people of Minangkabau, a tribe in Indonesia, migrated to Malaysia to look for a greener pasture. Recent visit in West Sumatra has shown that the once glorious regional architecture is slowly disappearing due to the growing interest in modern movement of architecture. Even worse, the fading interest on regional architecture among the people of Minangkabau in Negeri Sembilan is growing in a faster rate that it is very rare to see newly built building having the Minangkabau style. This research aims at evaluating the losing interest in regional architecture among the people of Minangkabau, and among architects in both countries, Malaysia and Indonesia. The discussion covers relevant literature of the origin of Minangkabau Architecture, aspects that contribute to its appreciation and factors that influence its decline. This literature review has the purpose of identifying the advantages and disadvantages of preserving and constructing buildings with Minangkabau style in current world of globalisation, thus, analysing whether promoting for the revival of Minangkabau style in both regions might be worthy or not.